2010
DOI: 10.1021/ic100304z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Metal Orbital Hybridization in Sulfur-Bearing Compounds Studied by X-ray Emission Spectroscopy

Abstract: The electronic structure and ligand environment of sulfur was investigated in various sulfur-containing compounds with different structures and chemical states by using X-ray emission spectroscopy (XES). Calculations were performed using density functional theory (DFT) as implemented in the StoBe code. The sulfur chemical state and atomic environment is discussed in terms of the molecular orbitals and partial charges that are obtained from the calculations. The main spectral features can be modeled using our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 39 publications
4
69
0
Order By: Relevance
“…The intensity ratio of Kβ'/Kβ 1,3 varies depending on the binding form of S and can be used for speciation analysis [31][32][33][34]. At the Kα-line a small energy shift in dependence of the binding form can be observed when spectrometers with an extremely good angle resolution are used [35].…”
Section: Xrf-analysismentioning
confidence: 99%
“…The intensity ratio of Kβ'/Kβ 1,3 varies depending on the binding form of S and can be used for speciation analysis [31][32][33][34]. At the Kα-line a small energy shift in dependence of the binding form can be observed when spectrometers with an extremely good angle resolution are used [35].…”
Section: Xrf-analysismentioning
confidence: 99%
“…This and closely related approaches have been used to study the XES of a wide range of systems. [45][46][47][48] Equation (1.2) shows the oscillator strength computed within the dipole approximation; for heavy nuclei it has been observed that the quadrupole contribution to the transition moment can be significant. 49 Simulating XES directly from the Kohn-Sham calculation is computationally less expensive than TDDFT, since the additional TDDFT calculation is not required and the spectra for all core orbitals can be obtained from the same calculation.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray Emission Spectroscopy (XES) and Resonant Inelastic X-ray Scattering (RIXS) are very powerful in elucidating the electronic structure, providing information on the electron energies, local geometry, spin and valence state, etc. [9,17,18,19,20,21,22,23]. These tools can thus deliver complementary information to the usually employed ultrafast laser spectroscopies, when implemented in a pump-probe experiment with a laser pump and a time-delayed X-ray probe pulse.…”
Section: Introductionmentioning
confidence: 99%